Energy Savings via Dead Sub-Block Prediction - Alves, Marco A. Z.; Khubaib, Khubaib; Ebrahimi, Eiman; Narasiman, Veynu T.; Villavieja, Carlos; Navaux, Philippe O. A.; Patt, Yale N. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2012)
Cache memories have traditionally been designed to exploit spatial locality by fetching entire cache lines from memory upon a miss. However, recent studies have shown that often the number of sub-blocks within a line that are actually used is low. Furthermore, those sub-blocks that are used are accessed only a few times before becoming dead (i.e., never accessed again). This results in considerable energy waste since 1) data not needed by the processor is brought into the cache, and 2) data is kept alive in the cache longer than necessary. We propose the Dead Sub-Block Predictor (DSBP) to predict which sub-blocks of a cache line will be actually used and how many times it will be used in order to bring into the cache only those sub-blocks that are necessary, and power them off after they are touched the predicted number of times. We also use DSBP to identify dead lines (i.e., all sub-blocks off) and augment the existing replacement policy by prioritizing dead lines for eviction. Our results show a 24% energy reduction for the whole cache hierarchy when averaged over the SPEC2000, SPEC2006 and NAS-NPB benchmarks.